Mechanical performance of composite retaining and protection structure for super large and deep foundation excavations - Cui, Zhen; Li, Qimin; Wang, Jian (Journal of Civil Engineering and Management, 2019)
The reliable retaining methods and a good stress system are the key to the success of super large and deep excavation engineering. In this paper, the deepest foundation pit in Hainan province is taken as an example. The method of mutual verification between in-situ monitoring and numerical simulation is adopted. The mechanical performance of composite retaining structure composed of reinforced concrete cast-in-situ soldier pile wall, diaphragm wall and prestressed anchor cable are studied. The interaction between the reinforced concrete cast-in-situ pile retaining structure at the upper part and the diaphragm wall retaining structure at the lower part is revealed, and the variation of internal forces of the diaphragm wall retaining structure in the time and space is demonstrated. And then the influence of insertion ratio and rigidity on the mechanical properties of diaphragm wall is discussed. Research shows, the range of interaction between the upper and lower retaining structures is limited. During the excavation process, the maximum bending moment of the diaphragm wall is always near the excavation surface, and the curvature of the bending moment curve decreases gradually with the increase of excavation depth and axial tension of anchor. When the insertion ratio of diaphragm wall increases, the maximum bending moment moves upward. With the rigidity of the diaphragm wall increases moderately, the bending moment of the retaining structure increases, but the lateral displacement decreases. The research results can provide theoretical basis and practical experience for the composite retaining structure design of super large and deep foundation excavations.